In vitro antifungal effect of mouth rinses containing chlorhexidine and thymol - Ashish Shrestha; Jyotsna Rimal; Ashwini Rao; Peter Simon Sequeira; Dolar Doshi; Gopal Krishna Bhat (Elsevier, 2011)
Background/purpose: In this in vitro study, we assessed the antifungal effect of mouth rinses containing chlorhexidine and thymol. Materials and methods: The fungistatic activities of chlorhexidine- and thymol-containing mouth rinses were assessed by means of the minimum inhibitory concentration (MIC) and the fungicidal activity was determined by a time-kill assay. Results: The chlorhexidine-containing mouthwash was able to kill all strains of Candida albicans and Candida tropicalis in shorter times compared to the thymol-containing mouthwash. Hexidine showed an MIC of 1:32 for both Candida species, whereas Listerine respectively showed MICs of 1:8 and 1:16 for C. albicans and C. tropicalis. Conclusions: Antimicrobial agents used in the study had good in vitro activity against the two Candida species. Mouth rinses containing chlorhexidine showed superior antifungal and fungicidal activities compared to the thymol-containing mouth rinse. Both antimicrobial agents may be suggested for use as topical antifungal agents.